GENDER DIFFERENCES IN MOTIVATIONS FOR LEARNING CHINESE: A CASE STUDY OF UNDERGRADUATE STUDENTS IN MALAYSIA - Lee Hui Ling; Balazs Huszka (BAHAS, 2018)
For the past few years, undoubtedly due to China’s growing economic status, there has been a significant increase in the number of students learning Chinese. As a third language in university curricula in Malaysia, it also enjoys a popularity never seen previously. From the angle of didactics, therefore, it is indeed of particular importance to carry out a multi-perspective research on motivations of Malaysian learners behind choosing Chinese as a foreign language. Based upon our experience, there is a remarkable gender difference in this field. This study examined these differences in motivation for learning Chinese amongst undergraduate students in Malaysia. A representative sample of 75 participants was selected from elementary level Chinese classes at Universiti Malaysia Kelantan. Findings of the investigation, based on a questionnaire, were analyzed by the software ‘IBM SPSS Statistics’. The analysis of the data revealed that female participants look at the practicability of the language when learning Chinese, whereas male participants are motivated primarily by their social responsibility and the learning situation. An overall analysis of the variables showed that male participants received a higher mean value in ‘learning situation’ only, and female participants were rather dominant in respect of ‘individual development’, ‘social responsibility’, ‘task value’, ‘information medium’, ‘self-efficacy’ and ‘intrinsic interest’. Through awareness of these gender-driven differences, both teaching and learning efforts can be optimized in the didactics of Chinese at universities in Malaysia.